2008
DOI: 10.1038/onc.2008.355
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of glioma cell survival by acyl-CoA synthetase 5 under extracellular acidosis conditions

Abstract: Extracellular acidosis (low pH) is a tumor microenvironmental stressor that has a critical function in the malignant progression and metastatic dissemination of tumors. To survive under stress conditions, tumor cells must evolve resistance to stress-induced toxicity. AcylCoA synthetase 5 (ACSL5) is a member of the ACS family, which converts fatty acid to acyl-CoA. ACSL5 is frequently overexpressed in malignant glioma, whereas its functional significance is still unknown. Using retrovirusmediated stable gene tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 41 publications
2
57
0
Order By: Relevance
“…However, additional studies are required to determine the functional significance of DNA methylation, if any, at these genes. Our finding of differentially methylated/accessible genes previously shown to harbor mutations in GBM-COL19A1 (Sumiyoshi et al 1997), CD93 (Dieterich et al 2012), AGAP2 (Knobbe et al 2005), and ACSL5 (Mashima et al 2009)-supports the validity of this approach in identifying GBM-relevant epigenetic perturbations. Interestingly, most of the genes that were identified as differentially methylated between GBM and NSC were classified as variably methylated in NSC (Table 4, lower).…”
Section: Discussionsupporting
confidence: 77%
“…However, additional studies are required to determine the functional significance of DNA methylation, if any, at these genes. Our finding of differentially methylated/accessible genes previously shown to harbor mutations in GBM-COL19A1 (Sumiyoshi et al 1997), CD93 (Dieterich et al 2012), AGAP2 (Knobbe et al 2005), and ACSL5 (Mashima et al 2009)-supports the validity of this approach in identifying GBM-relevant epigenetic perturbations. Interestingly, most of the genes that were identified as differentially methylated between GBM and NSC were classified as variably methylated in NSC (Table 4, lower).…”
Section: Discussionsupporting
confidence: 77%
“…Further four genes [namely, midkine (MDK), caspase 1 (CASP1), vitamin D receptor (VDR), and protein-L-isoaspartate O-methyltransferase (PCMT1)], for which the results were significantly correlated in our analyses (with MDK, CASP1 and VDR being positively correlated to TMZ resistance, and PCMT1 negatively correlated to TMZ resistance) (Fig. 2), have previously been reported to be associated with chemotherapy resistance, prognosis, tumor progression, or antiproliferation, in malignant gliomas (25)(26)(27)(28)(29).…”
Section: Resultsmentioning
confidence: 54%
“…However, again, none of these genes were identified in our microarray analysis. On the other hand, highly significant statistically positive-and negative-correlation of genes concerned with TMZ sensitivity/resistance were found as shown in Tables II and III (25)(26)(27)(28)(29), were differentially expressed in association with TMZ sensitivity/resistance in the glioma-derived cell lines. Among the genes positively correlated to TMZ resistance in our analysis, one of the most noteworthy is MGMT, as mentioned above; MGMT expression provides a resistance measure that can potentially be applied to current TMZ-based treatment strategies for malignant glioma patients.…”
Section: Discussionmentioning
confidence: 99%
“…ACSL5, another ACS isoform, plays a role in the pathogenesis of cancer. It is frequently overexpressed in malignant gliomas and is involved in their growth and survival (Yamashita et al, 2000;Mashima et al, 2009). Studies with a specific inhibitor of ACS, Triacsin c, further revealed that ACS inhibition induces selective apoptosis in cancer cells through the mitochondria-mediated pathway (Mashima et al, 2005).…”
Section: Acyl-coa Synthetasementioning
confidence: 99%